Muscle co-activation and its influence on running performance and risk of injury in elite Kenyan runners - Tam, N.; Santos-Concejero, J.; Coetzee, D. R.; Noakes, T. D.; Tucker, R. (Journal of Sports Sciences, 2017)
The relationship between muscle co-activation and energy cost of transport and risk of injury (initial loading rate and joint stiffness) has not been jointly studied. Fourteen elite Kenyan male runners were tested at two speeds (12 and 20 km/h), where oxygen consumption, kinematic, kinetic and electromyography were recorded. Electromyography of seven lower limb muscles was recorded. Pre-activation and ground contact of agonist:antagonist co-activation was determined. All muscles displayed higher activity during pre-activation except rectus femoris (RF). Conversely, no differences were found during ground contact except for higher biceps femoris (BF) at 20 km/h. Knee stiffness was correlated to RF-BF co-activation during both pre-activation and ground contact at both running speeds. However, energy cost of transport was only positively correlated to the above-mentioned muscle pairs at 20 km/h (r = 0620, P = 0.032; r = 0.682, P = 0.015, respectively). These findings emphasise the influence of neuromuscular control and performance and its support to musculoskeletal system to optimise function and modulate risk of injury. Further, neuromuscular activity during terminal swing is also important and necessary to execute and maintain performance.